2004
DOI: 10.1023/b:conc.0000039128.78645.a8
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Fatty-Acid Ethanolamides from Linum catharticum Oils and Cololabis saira Fats

Abstract: and mixtures of ethanolamides of fatty acids from natural fats (oils) were synthesized. It was found that the polyunsaturated fatty acids did not isomerize under the proposed conditions for aminolysis of the ester bond. Conditions for analyzing the complicated mixtures of ethanolamides of fatty acids by HPLC-MS were determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Most commonly, direct conversion of FAG to FAAA has been studied using ethanolamine as a solvent with ,, or without sodium methoxide catalyst. A conversion of FAG to FAAA through fatty acid methyl ester (FAME) has also been reported with analogous reaction conditions and with excellent yields for both steps …”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Most commonly, direct conversion of FAG to FAAA has been studied using ethanolamine as a solvent with ,, or without sodium methoxide catalyst. A conversion of FAG to FAAA through fatty acid methyl ester (FAME) has also been reported with analogous reaction conditions and with excellent yields for both steps …”
Section: Introductionmentioning
confidence: 94%
“…A number of studies have reported conversion of fatty acid triglycerides (FAG) from terrestrial biomass (i.e., vegetable oil) to alkanolamides. , In general, FAAA can be synthesized from alkanolamine with a fatty acyl donor, such as free fatty acids, fatty acid chlorides, fatty acid alkyl esters, and FAG. , Acyl chlorides have been used to deliver FAAA products with sufficient purity for biological studies , but are likely unsuitable for industrial-scale production because of cost and the corrosive nature of the reagents. Fatty acid conversion to FAAA can be accomplished using sodium methoxide catalyst but requires harsh reaction conditions due to ionic salt formation .…”
Section: Introductionmentioning
confidence: 99%
“…As there was no commercially available reference standard of THEA, we first confirmed that any signal obtained by MS was not the result of a molecule of identical mass and retention time. Therefore, it was necessary to synthesize a THEA standard from accepted methodologies (29). Importantly, we first assessed our synthesis protocol for DHEA so that we could compared it to a commercially available DHEA standard and were then able to synthesize and purify a THEA standard that could be used for accurate identification of THEA in mouse whole brain.…”
Section: Discussionmentioning
confidence: 99%
“…Methods for DHEA and THEA synthesis were adopted from Karaulov et al (29). Briefly, DHA (Nu-Chek Prep, Inc., Elysian, MN) and THA methyl esters (Larodan, Inc., Monroe, MI) were treated with fresh monoethanolamine (1:5 molar ratio; Millipore-Sigma, Burlington, MA) and trifluoroacetic acid (Millipore-Sigma).…”
Section: Organic Synthesis Of Dhea and Theamentioning
confidence: 99%